PENYUSUNAN PROJECT PLANNING PERBAIKAN TANAH LUNAK DENGAN PREFABRICATED VERTICAL DRAIN (STUDI KASUS PADA AREA LONG BEACH PAKUWON CITY-SURABAYA) - Amin Fahmi, Muhammad (Prokons: Jurnal Teknik Sipil, 2013)
The improvement project was carried out within 30 work days with the project price of IDR 551.439.500,-. In the project management a project planning is in need a carry out the project on time at precise cost and quality. The data needed in this arrangement of project planning were contract documents, list of work force cost, equipment and materials used. Work scheduling and cost arrangement for the project was done with benefit of Microsoft Project Program. The writer discusses the determination of project site layout, traffic management, implementation method, project time schedule, project cost planning, project quality management planning as well as K3 program planning. From the calculating result, the writer summed that the total cost was Rp. 270.950.000.-. When this sum compared to the previous project cost planning was Rp. 551.439.500,- we can difference as much as Rp. 280.489.500.-. In order to assure the working quality, material testing was conducted in laboratory so that the material mounted matched the technical qualifications as well as the use if correct implementation method. To avoid work accident, every worker must use the Self Protection Device and work carefully by the correct working procedures. Keywords:  Vertical Drain, Soft Clay, Project Planning